Fiber and whisker reinforced ceramics for structural applications - Belitskus, David (Materials engineering (Marcel Dekker, Inc.), 1993)
Examines various important aspects of whisker and fibre reinforced ceramic science and technology, offering an account of developments in the field. This work shows how to improve the strength and stiffness of ceramic composites, at very high temperatures, without brittleness.